The Influence of Free Cash Flow, Financial Distress, and Investment Opportunity Sets on Profit Management (Studies in Transportation Companies Registered at Indonesia Stock Exchange Period 2019 - 2022) - Syabila Mardhiyani; Preatmi Nurastuti; Adrianna Rakhmat (Jurnal Penelitian Ekonomi dan Akuntansi (JPENSI), 2023)
Fiscal reports used to measure profit operations results. Reported profits are very useful for stakeholders and investors to encourage company management to execute strategic plans and produce reports that stakeholders expect to be referred to as profit management. The study aims to identify profit management practices in transport companies listed on the Indonesia Stock Exchange period 2019–2021 as a result of free cash flow, financial distress and investment opportunity set. The sampling method uses Purposive sampling with the criteria that have been selected, so that 44 samples from 11 companies are obtained. The study is quantitative with the Double Regression Analysis method with SPSS 29.0 software aids. The results of the test showed that the Investment opportunity set has a significant positive value for profit management, while for free cash flow and Financial distress have no significant value for profit management.